Effects of iron-deficient diet on sleep onset and spinal reflexes in a rodent model of Restless Legs Syndrome - Woods, Sydney; Basco, Joseph; Clemens, Stefan (Frontiers in Neurology, 2023)
Restless Legs Syndrome (RLS) is a common sensorimotor and a sleep disorder that affects 2.5–10% of the European and North American populations. RLS is also often associated with periodic leg movements during sleep (PLMS). Despite ample evidence of genetic contributions, the underlying mechanisms that elicit the sensory and motor symptoms remain unidentified. Clinically, RLS has been correlated with an altered central iron metabolism, particularly in the brain. While several animal models have been developed to determine the outcome of an altered iron homeostasis on brain function, the potential role of an altered iron homeostasis on sleep and sensorimotor circuits has not yet been investigated. Here, we utilize a mouse model to assess the effects of an iron-deficient (ID) but non-anemic state on sleep time and episodes, and sensorimotor reflexes in male and female mice. We found that animals on the ID diet displayed an increased expression of the transferrin receptor in the spinal cord, confirming the results of previous studies that focused only on the impact of ID in the brain. We also demonstrate that the ID diet reduced hematocrit levels compared to controls but not into the anemic range, and that animals on the ID diet exhibited RLS-like symptoms with regard to sleep onset and spinal cord reflex excitability. Interestingly, the effects on the spinal cord were stronger in females than in males, and the ID diet-induced behaviors were rescued by the return of the animals to the control diet. Taken together, these results demonstrate that diet-induced ID changes to CNS function are both inducible and reversible, and that they mimic the sleep and sensorimotor RLS symptoms experienced in the clinic. We therefore propose replacing the commonly used phrase “brain iron deficiency” (BID) hypothesis in the RLS research field with the term “iron deficiency in the central nervous system” (ID-CNS), to include possible effects of altered iron levels on spinal cord function.